NEUROD2 function is dispensable for human pancreatic β cell specification - Cota, Perla; Saber, Lama; Taskin, Damla; Jing, Changying; Bastidas-Ponce, Aimée; Vanheusden, Matthew; Shahryari, Alireza; Sterr, Michael; Burtscher, Ingo; Bakhti, Mostafa; Lickert, Heiko (Frontiers in Endocrinology, 2023)
The molecular programs regulating human pancreatic endocrine cell induction and fate allocation are not well deciphered. Here, we investigated the spatiotemporal expression pattern and the function of the neurogenic differentiation factor 2 (NEUROD2) during human endocrinogenesis. Using Crispr-Cas9 gene editing, we generated a reporter knock-in transcription factor (TF) knock-out human inducible pluripotent stem cell (iPSC) line in which the open reading frame of both NEUROD2 alleles are replaced by a nuclear histone 2B-Venus reporter (NEUROD2nVenus/nVenus). We identified a transient expression of NEUROD2 mRNA and its nuclear Venus reporter activity at the stage of human endocrine progenitor formation in an iPSC differentiation model. This expression profile is similar to what was previously reported in mice, uncovering an evolutionarily conserved gene expression pattern of NEUROD2 during endocrinogenesis. In vitro differentiation of the generated homozygous NEUROD2nVenus/nVenus iPSC line towards human endocrine lineages uncovered no significant impact upon the loss of NEUROD2 on endocrine cell induction. Moreover, analysis of endocrine cell specification revealed no striking changes in the generation of insulin-producing β cells and glucagon-secreting α cells upon lack of NEUROD2. Overall, our results suggest that NEUROD2 is expendable for human β cell formation in vitro.